Treatment of experimental periodontal disease by laser therapy in simvastatin-modified rats - Andressa Araújo SWERTS; Bianca Fernanda Espósito SANTOS; Simone Ribeiro BRUZADELLI; Maísa Ribeiro Pereira Lima BRIGAGÃO; Daniela Coelho de LIMA; Leandro Araújo FERNANDES
Abstract Low intensity laser can be used as a promising alternative in the treatment of periodontal disease. Objective The aim of this study was to evaluate low-level laser therapy (LLLT) as an adjuvant treatment for scaling and root planing (SRP) for the treatment of induced periodontitis in simvastatin-modified rats. Material and Methods A total of 180 rats were evenly divided into two groups: Veh - receiving oral administration of polyethylene glycol (vehicle); S - receiving oral administration of Simvastatin. Periodontal disease was induced in both groups at the first mandibular molar. After seven days, the ligature was removed and the animals were divided into subgroups according to the following local treatments: NT - no treatment; SRP - scaling and root planing and irrigation with saline solution; and LLLT ¬- SRP and laser irradiation (660 nm; 0.03 W; 4 J). Ten animals in each subgroup/local treatment were euthanized at 7, 15 and 30 days. Samples of gingival tissue were processed to analyze the tissue oxidative damage and radiographic analysis. Levels of oxidative stress were analyzed by the expressions of Tripeptideglutathione (TG), Malondialdehyde (MDA) and Carbonylated Proteins (CP). Results The animals in S group had higher levels of TG and lower levels of MDA and CP compared with Veh group (p<0.05). Radiographically, in the intragroup analysis Veh and S, LLLT showed lower bone loss (BL) compared with NT and SRP, in all experimental periods (p<0.01). In addition, a lower BL was observed for the animals of Veh group treated with LLLT compared with treatment SRP in the S group, in all experimental periods. Conclusion Within the limits of this study, we can conclude that LLLT was effective as adjuvant treatment for SRP protecting against the occurrence of oxidative tissue damages as well as for reducing alveolar bone loss in experimentally induced periodontitis simvastatin-modified rats.